Effect of the modification structure for Newton’s metal on some its properties for industrial applications - Kashita, Eman (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Newton’s metal is important for industrial applications that is the reason for studying the effect of modified structure of it’s on mechanical and thermal properties. Microstructure, mechanical properties such as elastic modulus Vickers hardness, internal friction and melting temperature of Bi50Pb34Sn16, Bi50Pb28Sn22, Bi50Pb22Sn28 and Bi50Pb16Sn34 alloys have been studied and analyzed. X-ray analysis of these alloys show that, it contained different phases with formed a solid solution. Elastic modulus variable decrease, melting temperature varied, internal friction and Vickers hardness increased due to modified Newton’s metal (Bi50Pb31.2Sn18.8) alloy.